MANTRA TRADISI CEMME PASSILI MASYARAKAT BUGIS KABUPATEN MAROS : TINJAUAN SEMIOTIKA RIFATERRE - Fahrir, Hasvivi Tri Anjar Sari; Nensilianti, Nensilianti; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe (1) The ins and outs of expression in the purpose of cemme passili traditional magical formula the buginees maros (2) The meaning contained in the purpose of cemme passili traditional magical formula the buginees maros based on heuristic and hermeneutic readings. This type of research is quality research. This result is: (1) the ins and outs of expression managed to find the meaning contained in the purpose of cemme passili traditional magical formula the buginees Maros based on the replacement of meaning, deviation of meaning and creation of meaning; (2) Heuristic readings using Indonesian conventions, while hermeneutic readings show the hope of The Purpose Of Cemme Passili to prevent brides to be from unwanted things.